2022
DOI: 10.6007/ijarafms/v12-i2/14114
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Board Diversity and Corporate Performance in Malaysia: Pre- and During COVID-19 Pandemic

Abstract: The objective of this study, which is based on the upper echelon theory, managerial networking theory and agency theory, is to investigate the influence of board diversity on the performance of Malaysian Pharmaceutical Listed Companies. The information was gathered from pharmaceutical businesses listed on the Bursa Malaysia Berhad from 2015 to 2020. Because the data comprises observations on distinct company parts throughout time, the fixed effects model is used to address the endogeneity problem. We discovere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Against the backdrop of the 2008 global financial crisis, both Chen et al (2019) and Papangkorn et al (2021) found that board gender diversity can effectively stave off declines in firm performance and may even enhance it. Similarly, Shamsudin et al (2022), Amorelli and García-Sánchez (2023), in the context of the COVID-19 pandemic, concluded that board gender diversity holds promise in bolstering firm performance and mitigating the extent of setbacks experienced by firms. Additionally, Azeem et al (2023) examined the impact of board gender diversity on firm financial resilience during the COVID-19 pandemic, suggesting that while it brings diverse analytical perspectives, it may also lead to internal conflicts.…”
mentioning
confidence: 99%
“…Against the backdrop of the 2008 global financial crisis, both Chen et al (2019) and Papangkorn et al (2021) found that board gender diversity can effectively stave off declines in firm performance and may even enhance it. Similarly, Shamsudin et al (2022), Amorelli and García-Sánchez (2023), in the context of the COVID-19 pandemic, concluded that board gender diversity holds promise in bolstering firm performance and mitigating the extent of setbacks experienced by firms. Additionally, Azeem et al (2023) examined the impact of board gender diversity on firm financial resilience during the COVID-19 pandemic, suggesting that while it brings diverse analytical perspectives, it may also lead to internal conflicts.…”
mentioning
confidence: 99%